Analisis Faktor Determinan yang Mempengaruhi Kinerja Organisasi Rumah Sakit (RS) Swasta - Gen Norman Thomas (Bina Nusantara University, 2015)
This study aims to reveal and clarify the influence of organizational culture, organizational commitment and public accountability to the organizational performance of Private Hospital in West Jakarta. This research is a quantitative study by the research method takes a sample of the population private hospitals in West Jakarta with respondent Hospital Director, Finance Manager, Marketing Manager, Research and Development Manager or HRD Manager for 40 people. Data was collected using a questionnaire to obtain data primier then it is processed using SPSS. The quality of the data was tested by using the validity test shows the data is valid, the reliability test obtain realible and classic assumptions test have normal curves, no multicollinearity and does not occur heterocedastity. The results of this study show the first hypothesis that the organizational culture (X1) showed no significant effect on the performance of private hospitals (Y). The second hypothesis indicates that organizational commitment (X2) does not affect the performance of private hospitals (Y). The third hypothesis testing shows that public accountability (X3) has a significant influence on the performance of private hospitals (Y). The fourth hypothesis that organizational culture (X1), organizational commitment (X2), and public accountability (X3) simultaneously have a significant influence on the organizational performance of private hospitals (Y).